2008
DOI: 10.1143/jjap.47.2848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rapid Thermal Annealing on the Electrical Characteristics of ZnO Thin-Film Transistors

Abstract: Thin-film transistors (TFTs) with a bottom-gate configuration were fabricated with an RF magnetron sputtered undoped zinc oxide (ZnO) channel layer and plasma-enhanced chemical vapor deposition (PECVD) grown silicon nitride as a gate dielectric. Postfabrication rapid thermal annealing (RTA) and subsequent nitrous oxide (N 2 O) plasma treatment were employed to improve the performance of ZnO TFTs in terms of on-current and on/off current ratio. The RTA treatment increases the on-current of the TFT significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…Oxygen vacancies can be reduced by thermal annealing in air atmosphere and would reduce the n-type character of the semiconductor [14]. According to reference [5], the oxygen vacancy density is much higher at the surface than in the bulk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen vacancies can be reduced by thermal annealing in air atmosphere and would reduce the n-type character of the semiconductor [14]. According to reference [5], the oxygen vacancy density is much higher at the surface than in the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Each sample was heated during 1 h at 300 °C, with a temperature ramp-up of 30 min. The aim of the thermal treatment was to oxidize the film to decrease the carrier concentration by reducing the oxygen vacancy density [14] or by chemisorption of oxygen at the ZITOs surface and nano-grain boundaries. The morphology of the samples was previously characterized by X-Ray Diffraction Spectroscopy and High-Resolution Transmission Electron Microscopy [15].…”
Section: Methodsmentioning
confidence: 99%
“…One effective routine to obtain TFTs with good performance is to deposit ZnO channel layer with higher resistivity and then to treat with post-annealing. Although many groups have reported that the post-annealing is an effective way to improve the performance of TFTs fabricated at room temperature, [10][11][12][13][14] few study has been studied on the performance evolution by post-annealing treatment. And the mechanism of how annealing treatment improves the performance of ZnO TFTs is rarely discussed as well.…”
Section: Introductionmentioning
confidence: 99%
“…3 When used as the active channel layer in TFTs, the deposition parameters of ZnO can be optimized to achieve high mobility, [4][5][6][7][8][9] low threshold voltage, 4 and high current ratios (I on / I off ). 6,10 The channel mobility is directly related with the crystalline quality of the semiconductor active layer, and it can be improved by employing epitaxial deposition techniques 8,9 and/or by postdeposition annealing treatment. 7 Zinc oxide thin films have been fabricated using several deposition techniques such as chemical vapor deposition (CVD), 11 pulsed laser deposition (PLD), 12 spin coating, 13 atomic layer deposition (ALD), 14 laser molecular-beam epitaxy (L-MBE), 8,9 and radiofrequency (RF) magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%